2019
DOI: 10.1093/jmcb/mjy084
|View full text |Cite
|
Sign up to set email alerts
|

News about non-secretory exocytosis: mechanisms, properties, and functions

Abstract: The fusion by exocytosis of many vesicles to the plasma membrane induces the discharge to the extracellular space of their abundant luminal cargoes. Other exocytic vesicles, however, do not contain cargoes, and thus, their fusion is not followed by secretion. Therefore, two distinct processes of exocytosis exist, one secretory and the other non-secretory. The present review deals with the knowledge of non-secretory exocytosis developed during recent years. Among such developments are the dual generation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
(222 reference statements)
0
3
0
Order By: Relevance
“…The intracellular amount of SRF in 4T1 cells decreased during the incubation with fresh media, which indicated that SRF was continuously expelled to the outside of the cells via exocytosis (Figure 2C). [ 22 ] Compared with cells exposed to SRF alone, CAGE‐exposed cells exhibited increased amounts of SRF remaining inside 4T1 cells, which suggests that exocytosis of SRF was decreased in the CAGE group. In particular, at the 30 and 60 min time points, exocytosis of SRF by 4T1 cells was significantly different between the two groups (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular amount of SRF in 4T1 cells decreased during the incubation with fresh media, which indicated that SRF was continuously expelled to the outside of the cells via exocytosis (Figure 2C). [ 22 ] Compared with cells exposed to SRF alone, CAGE‐exposed cells exhibited increased amounts of SRF remaining inside 4T1 cells, which suggests that exocytosis of SRF was decreased in the CAGE group. In particular, at the 30 and 60 min time points, exocytosis of SRF by 4T1 cells was significantly different between the two groups (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ replenishment caused an increase in uptake (Figure 3B), indicating the restoration of the exchangeable compartment, however. A large pool of non-secretory exocytotic vesicles is present in the cell, that can serve as a reserve pool of membrane for increasing the capacity of this compartment (see for review, (D’Alessandro and Meldolesi, 2019)).…”
Section: Resultsmentioning
confidence: 99%
“…NPs can be released from cells via exocytosis, which is distinguished by two main mechanisms: regulated exocytosis and constitutive exocytosis. Regulated exocytosis occurs when the contents of an intracellular vacuole are secreted from the cell in response to a specific signal, whereas constitutive exocytosis does not require a signal to secrete the macromolecules [ 11 , 12 ]. Cell internalisation and exocytosis pathways are of importance when considering the design and application of drug-loaded nanocarriers [ 13 ], and repeated endocytic and exocytic processes might be exploited by appropriately-designed NPs to enable ‘hopping’ of the carriers through multiple cell layers in order to enhance penetration through brain parenchyma.…”
Section: Introductionmentioning
confidence: 99%